STRATEGIC OVERVIEW OF FINANCIAL SUPPORT FOR THE DEVELOPMENT OF SMALL INNOVATIVE ENTERPRISES IN UKRAINE (World of finance, 2019)
Introduction. Small innovative businesses play an important role in the economy of developed countries and are an essential element of the innovation process. Small enterprises are the most flexible, dynamic and widespread form of enterprises.Ukraine’s aspiration to European integration necessitates the introduction of an innovative model of development, one of the components of which is the development of a domestic innovation enterprise, which prompts to seek new approaches to the implementation of scientific, technical and innovative potential of the country’s economy.The purpose of the article is to find out the features and problems of financial support for the development of small innovative enterprises in Ukraine and to substantiate directions for its improvement.Results. According to the data of the State Statistics Service of Ukraine, innovation activity in Ukraine in 2018 was carried out only by every eleventh enterprise. The share of enterprises that introduced innovations in 2017 amounted to 16.2%, and those engaged in innovations 14.3%, respectively. At the same time, the share of innovative products in the total industrial volume was, according to the results of 2017, only 0.7%. In Ukraine, as of January 1, 2018, in the total number of enterprises (338256 units), the share of small business entities amounted to 95.5%. This testifies to the dependence of the level of development of the Ukrainian economy on their innovative activity.Among the range of obstacles to the successful functioning of innovative entrepreneurship, the problem of low efficiency of functioning of the financial mechanism of ensuring their development is the most urgent. Particular attention should be paid to the use of national competitive advantages, avant-garde industries, high-tech industries, such as space technology, aviation industry, biotechnology, tool manufacture, defense and industrial complex. Innovation demand in Ukraine should become not only an economic category but also an essential property of a person’s character.Conclusions. The development of innovative entrepreneurship is not carried out quickly and purposefully. Its potential, as the main tool for commercializing scientific ideas, is practically not implemented in Ukraine. Before small innovative enterprises, there are many barriers and obstacles that prevent them from working effectively.Thus, in order to provide effective financial support for the development of small innovative entrepreneurship, it is necessary, first of all, to improve the financial and tax policy of supporting small businesses, as well as to increase the efficiency of the use of established institutions of market infrastructure for supporting small businesses. The details of the mechanisms for implementing these measures should be the subject of further research, the results of which will be highlighted in the following publications.